Implementation of the human talent management through competencies model in a university in Metropolitan Lima - C. Rodríguez, Juan (2015)
This article is a work proposal that aims to describe the methodology proposed by the Management of Personnel Management from a university in Lima, to implement a management model based on competencies which traceability involves various technical HR processes practiced in the organization and is aligned to institutional outcomes defined in the balance score card. In order to do it, various literature sources were consulted, and the websites of the top ten universities worldwide to identify benchmarks were visited. Generic skills, competencies level, specific skills, competencies dictionary and graduation for each of the managements, occupational categories and administrative headquarters of the University: as a result, the following definitions and elements were obtained. In this way, the institution develops a tool to guide how and to what extent human resources should have and develop skills to achieve specific organizational results.